(untitled) (Bangladesh Journal of Botany, 2025)
An investigation was conducted to assess the efficacy and crop tolerance of Almix 20WP, a herbicide premix of metsulfuron-methyl and chlorimuron-ethyl, for controlling sedges and broadleaf weeds in flooded rice fields. Treatments included various rates of Almix 20WP, 2,4-D, Bentazone-sodium, Bispyribac-sodium, and a tank-mix of Almix 20WP (40 g/ha) with 2,4-D (1000 g/ha). Almix 20WP at 60 g/ha significantly reduced weed biomass and density. Bentazone-sodium treated rice yielded the highest grain (7975.0 kg/ha), with the tank-mix of Almix 20WP and 2,4-D provided the second-highest (7962.5 kg/ha). Almix 20WP showed excellent control of weeds like Cyperus difformis, Fimbristylis miliacea, and Ludwigia octovalvis, with the tank-mix enhancing control of Cyperus iria. Thus, Almix 20WP at 40 g/ha is recommended for flooded fields to control sedges and broad leaf weeds. Bangladesh J. Bot. 54(2): 185-190, 2025 (June)